Data mining using SAS applications CD-ROM [electronics resource] - Fernandez, George, 1952- (Boca Raton, FL : CRC Press, 2007)
Software requirements: Licensed SAS modules BASE, STAT, GRAPH, and IML, version 6.12 or higher; Microsoft Excel 97/2000 or 5.0/95; Microsoft Word to view RFT output; Adobe Acrobat Reader to view PDF output; Microsoft Internet Explorer or Netscape Navigator